A STUDY OF MATERNAL HEALTH SERVICES BY PRIVATE MIDWIVES IN SURABAYA CITY, INDONESIA - Betty Roosihermiatie; Arief Priyo Nugroho; Felly Philipus Senewe (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2023)
Maternal mortality in Indonesia increased but the coverage of antenatal care and birth attendants by health workers is high. The majority of antenatal care was by private midwives and the majority of birth attendants was by midwives. The study aims to determine the maternal health services by private midwives in maternal health services. It was a mixed study, carried out in Surabaya City because of the highest maternal deaths in East Java Province in 2016. The secondary data of maternal health services were collected from Surabaya City Health Office and Indonesian Midwives Association of Branch Surabaya City. The qualitative data were domain on internal and external problems of private practice midwives. There were 10 informants whom selected purposively. The data were collected by round table discussion. The secondary data were analyzed univariately and the qualitative data were analyzed descriptively. From about 250 private midwives in Surabaya City, 133 were ‘Delima’ midwives in which a program of the Indonesia Midwives Association. Maternal health services by private midwives enhance access. The ‘Delima’ midwives have requirements of knowledge, enhancing skill, reporting, infrastructure standards, and development. So, the quality of maternal health services by ‘Delima’ midwives was relatively better. However, private midwives’ services, including the ‘Delima’ midwives in Surabaya city had not analyzed ANC results, pregnant women visiting private midwives should visit health centers for integrated ANC, midwives’ duties beyond educational competencies, and lack of mentoring for apprentice midwives because of many midwives’ duties. It suggests improving the knowledge and skill of private midwives.